First Objective Association Between Elevated Carbohydrate‐Deficient Transferrin Concentrations and Alcohol‐Related Traffic Accidents. (27th October 2015) - Bortolotti, Federica; Micciolo, Rocco; Canal, Luisa; Tagliaro, Franco
Abstract : Background: Carbohydrate‐deficient transferrin (CDT) is a well‐recognized highly specific marker of chronic alcohol abuse. The association of CDT with alcohol‐related traffic accidents was evaluated to objectively validate the use of this marker for certifying the physical fitness for driving license regranting after its confiscation for drunk driving. Methods: The study was carried out on 468 injured drivers (InjDr), who underwent mandatory blood alcohol concentration (BAC) and drug analysis in biological fluids. The InjDr group was divided into 2 subgroups on the basis of BAC legal limit adopted in Italy (BAC ≤ 0.5 g/l: InjDr1 ; BAC >0.5 g/l: InjDr2 ). The control group (CntDr) included 236 subjects holding safety‐sensitive job positions and undergoing mandatory toxicological analyses. The determination of BAC in blood and CDT in serum were performed using validated analytical methods based on head‐space gas chromatography and high‐performance liquid chromatography, respectively. Results: The evaluation of CDT distribution in the 3 groups (CntDr, InjDr1, InjDr2 ) showed that CDT distribution in the InjDr1 group was similar to that observed in the CntDr group ( p = 0.159) and different from that observed in the InjDr2 group ( p < 0.001). Partitioning the CDT data of each group into "CDT positives" and "CDT negatives" on the basis of the cut off (1.90%), it was possible to calculate the odds of the 3 groups and then the odds ratios. The odds ratio of InjDr1 versus CntDr was 4.56 ( p = 0.158), whereas the odds ratio of InjDr2 versus CntDr was 132 ( p < 0.001). Furthermore, a dose–response effect was found only when comparing InjDr2 with CntDr. Conclusions: The data of the present study strongly support the use of the CDT test to evaluate the risk of a subject to be involved in a road accident while driving under the influence of alcohol.